2015
DOI: 10.1111/insr.12115
|View full text |Cite
|
Sign up to set email alerts
|

H‐likelihood Predictive Intervals for Unobservables

Abstract: Inferences about unobserved random variables, such as future observations, random effects and latent variables, are of interest. In this paper, to make probability statements about unobserved random variables without assuming priors on fixed parameters, we propose the use of the confidence distribution for fixed parameters. We focus on their interval estimators and related probability statements. In random-effect models, intervals can be formed either for future (yet-tobe-realised) random effects or for realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…For inferences of such models, Lee and Nelder (1996) proposed the use of the hlikelihood. Lee and Kim (2015) showed that inferences about unobservables allow both Bayesian and frequentist interpretations. In this paper, we see that the eTPR model is an extension of random-effect models.…”
Section: Predictive Distributionmentioning
confidence: 99%
“…For inferences of such models, Lee and Nelder (1996) proposed the use of the hlikelihood. Lee and Kim (2015) showed that inferences about unobservables allow both Bayesian and frequentist interpretations. In this paper, we see that the eTPR model is an extension of random-effect models.…”
Section: Predictive Distributionmentioning
confidence: 99%
“…The bootstrap method can also be used to calculate other quantities, such as the subject-specific random-effects. It can be considered as an extension of PIs 15 for random-effects to curve predictions.…”
Section: Inference Methodsmentioning
confidence: 99%
“…Existing PIs for subject-specific inferences often give liberal intervals as we shall show later. Lee and Kim 15 studied PIs for random-effect models and we extend them to HPFR models. The numerical studies show that the nominal confidence level (NCL) is well maintained using the approach.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the validity of joint maximization needs to be investigated on a model‐by‐model basis (Lee et al, 2006). When canonical scale is not certain, Lee and Kim (2016) suggested to use the predictive likelihood in Section 2.6.…”
Section: What Is H‐likelihood?mentioning
confidence: 99%
“…Lee and Kim (2016) further considered the confidence distribution (Xie & Singh, 2013) approach to construct interval estimators for unobservables. They showed that the interval estimator based on the plug‐in method is inconsistent unless θ and v are orthogonal.…”
Section: What Is H‐likelihood?mentioning
confidence: 99%